Diagnóstico das percepções de responsabilidade social empresarial a partir do modelo tridimensional de performance social: o caso de uma empresa do setor têxtil - Macêdo., Nívea Marcela M. Nascimento (2010)
Before the current context of businesses, the companies need to be prepared to the new economy and administration forms and to the new requirements of relevance and social performance, consolidated starting from the social actors‟ needs and problems involved with an organization. That context introduces to the companies a growing concern with your social legitimacy, because the valorization of the term Managerial Social Responsibility has been increasing in the last years. For a company to adopt and develop a posture based in ethical beginnings on parallel to the search of your economical objectives, she needs to have for base the stakeholders administration, once it will be like this possible to know the perspectives and needs of all the ones that they compose the institutional atmosphere and the means for better acceptability and application of your internal and external goals. The stakeholders are people with legitimate and authentic interests in relation to inherent aspects that influence the organization. A study that makes possible the explanation of the administration of your needs and perceptions becomes important because analyzes the actions and your impacts under the point of view of those that the build and use them. The objective of this research is like this to diagnose the perceptions of the several types of stakeholders concerning the politics and actions of social responsibility adopted by a textile company of the state of Paraíba, using the three-dimensional model of social performance of Carroll (1979), being one of the main contributions of this study the structuring of parameters so that the three-dimensional model in subject can be applied in a specific context. The methodology used in this study it consisted of a quali-quantitative research. The qualitative stage was based on interview routes semi-structured, and it was analyzed by the technique of content analysis; the quantitative was based on questionnaires created with base in the three-dimensional model, which were analyzed through the software sphinx. Some primary data were lifted up, as well as the observation non participant was done. Starting from this methodology it was verified the perceptions and understanding of the stakeholders concerning the social actions of the company, in that was possible to observe that the internal agents, employees in general and directors, believe that the researched company possesses more actions of legal nature, an accommodate answer and on employees focus. The external agents showed opinions more diversified, which they are based on your knowledge level on the concept of social responsibility, and to intrinsic characteristics yours, as the non readiness for a relationship more narrow or close with the organization. In that sense, it is ended that is of extreme urgency that the researched organization it takes including initiatives in the sense of a better interaction with your stakeholders. The understanding of those investigated was related to the reality of the company, however, the people didn't show great knowledge on the concept of the social responsibility, as well as they didn't sketch readiness to integrate or to act together in the social initiatives.